History Of Tuberculosis Contact And Tuberculin Test Result - Saputra, Angky; Nugraha, Jusak; Darmadi, Epriyanto T (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Tuberculosis (TB) is a chronic disease caused by Mycobacterium tuberculosis. History of tuberculosis contact has consequences for TB infection. Density of occupancy may also accelerate TB transmission. Tuberculin test is a screening method that can detect TB infection. However, BCG immunization can reduce the specificity of tuberculin test results because it causes false positive results. Aim: The aim of this study is to see the relationship between history of TB contact and tuberculin test results. Other variables related to tuberculin test results were also examined i.e. occupancy density and incidence of BCG immunization. Methods: This research was conducted with cross-sectional analytic design using contingency coefficient test with a value of ? = 0.1. TB contacts subjects were taken from Surabaya Pulmonary Hospital and non-TB contacts subjects were volunteers from Medical Faculty of Widya Mandala Catholic University volunteers and Medical Faculty of Wijaya Kusuma. Each group consisted of 25 people taken using consecutive sampling technique. There is a significant correlation between history of tuberculosis contact and tuberculin test (p = 0,000); There is no significant correlation between BCG immunization history and tuberculin test results (p = 0.221) Result: There is a significant correlation between occupancy density and tuberculin test results (p = 0.066). Conclusion: It can be concluded that history of tuberculosis contact and occupancy density are associated with positive tuberculin test results.